Current landscape of T-cell engagers in early-phase clinical development in solid cancers - Spinazzola, Andrea; Iannantuono, Giovanni Maria; Gulley, James L.; Giudice, Elena; Filetti, Marco; Sganga, Stefano; Bianco, Francesca Lo; Floudas, Charalampos S.; Daniele, Gennaro (Frontiers in Immunology, 2025)
T-cell engagers (TCEs) are an emerging class of immunotherapeutic agents designed to harness the immune system to target and eliminate cancer cells. These molecules bridge T lymphocytes with tumor cells, generating an immunologic synapse that leads to potent immune-mediated tumor destruction. Although the clinical activity of TCEs in patients with solid tumors remains insufficient, recent technological advancements have led to the development of several candidates in early-phase clinical trials, with some showing encouraging signs of efficacy. This review examines the current landscape of TCEs in early clinical development for the treatment of solid tumors, describing their mechanism, clinical progress, efficacy, and challenges.